The Number of Bacteria, Antioxidant Capacity, and Organoleptic Properties of Red Ginger Fried Chicken - Lismi Animatul Chisbiyah; Mazarina Devi; Issutarti Issutarti (Bulletin of Culinary Art and Hospitality, 2021)
Alpinia purpurata (Vieill.) K. Schum is a spice that has the ability to inhibit bacterial growth and has a good antioxidant capacity. This study aims to determine the effect of adding Alpinia purpurata (Vieill.) K. Schum 0%, 10%, 20%, 30%, 40% on day 0, 1, and 2 on the number of bacteria, antioxidant capacity and hedonic properties which include the taste, aroma, and color of Red ginger fried chicken. This type of research was an experimental research with a completely randomized factorial design (CRD). The data obtained were then analyzed statistically using ANOVA and continued with Duncan's Multiple Range Test (DMRT) to obtained differences. Each treatment was repeated twice. The results showed that the addition of the concentration of Alpinia purpurata (Vieill.) K. Schum 0%, 10%, 20%, 30% and 40% in Red ginger fried chicken had a significant effect on the number of bacteria and antioxidant capacity on day 0, 1, 2 and had a significant effect on the hedonic properties on day 0. (taste, color and aroma) on the hedonic properties on day 0. (taste, color and aroma). The addition of Alpinia purpurata (Vieill.) K. Schum 40% gave the best results on the number of bacteria, antioxidant capacity and hedonic properties. To conclude, the higher the addition of Alpinia purpurata (Vieill.) K. Schum to Red ginger fried chicken resulted on the lower the number of bacteria and the greater the antioxidant capacity and the more preferred hedonic properties.